1991
DOI: 10.1111/j.1530-0277.1991.tb00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Norharman (β‐Carboline) Levels are Elevated in Chronic Alcoholics

Abstract: Based on the hypothesis that condensation products of neurotransmitters with aldehydes are involved in the pathogenesis of alcoholism, aromatic beta-carbolines (norharman and harman) were measured in the blood plasma of alcoholics and nonalcoholics. The identity of the extracted compounds was confirmed by various elution conditions of the high performance liquid chromatography (HPLC), newly developed radioreceptor assays, and the mass spectrum of norharman. The levels of norharman and harman in nonalcoholics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
2
6

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 20 publications
2
55
2
6
Order By: Relevance
“…Therefore, we cannot assess the extent to which the case-control difference reflects a difference in dietary intake of harmane. However, our data indicate that log blood harmane concentration is not a function of time since last food consumption (r = -0.097, p = 0.49) and other investigators have demonstrated stable blood concentrations following food ingestion (Rommelspacher et al, 1991). Also, we did not assess liver function, variability in the cytochrome P450 system, or renal function to see whether factors that might influence the metabolism of harmane differed between cases and controls.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Therefore, we cannot assess the extent to which the case-control difference reflects a difference in dietary intake of harmane. However, our data indicate that log blood harmane concentration is not a function of time since last food consumption (r = -0.097, p = 0.49) and other investigators have demonstrated stable blood concentrations following food ingestion (Rommelspacher et al, 1991). Also, we did not assess liver function, variability in the cytochrome P450 system, or renal function to see whether factors that might influence the metabolism of harmane differed between cases and controls.…”
Section: Discussioncontrasting
confidence: 56%
“…The concentration remained stable. The same investigators also demonstrated that variability in concentration was minimal over a longer (three week) period (Rommelspacher et al, 1991). Our own data indicate that log blood harmane concentration is not correlated with the time latency since last food consumption (r = -0.097, p = 0.49 [N = 52]).…”
Section: Clinical Evaluationmentioning
confidence: 54%
See 2 more Smart Citations
“…Alcohol metabolism may lead to the formation of a beta-carboline compound called harman (33,34), and alcoholic beverages frequently contain harman (35), which has moderate affinity for MAO-A. To avoid temporary occupancy effects of harman (10), [ 11 C]-harmine PET scanning was timed at a point when harman levels were negligible (36), which was verified by plasma sampling.…”
Section: Protocol On Day Of Pet Imagingmentioning
confidence: 99%